Time Free From Hospitalization in Children and Adolescents With Cystic Fibrosis: Findings From FEV1, Lung Clearance Index and Peak Work Rate - Gambazza, Simone; Mariani, Alessandra; Brivio, Anna; Carta, Federica; Blardone, Chiara; Lisiero, Saba; Russo, Maria; Colombo, Carla (Frontiers in Pediatrics, 2022)
Background. Exercise test combined with multiple breath washout nitrogen test (MBWN2) may offer a comprehensive clinical evaluation of Cystic Fibrosis (CF) disease in children with normal spirometry. The purpose of the present study is to explore whether information derived from spirometry, MBWN2 and exercise test can help the CF multidisciplinary team to characterize time free from hospitalization due to pulmonary exacerbation in a cohort of pediatric patients with CF. Methods. This prospective observational study was carried out at the Lombardia Region Refer-ence Center for Cystic Fibrosis in Milano, Italy. From 2015, we consecutively enrolled children and adolescents aged <18 years with spirometry, MBWN2 and Godfrey exercise test performed during an outpatient visit. Results. Over a median follow-up time of 2.2 years (interquartile range, 2.01;3.18), 28 patients aged between 13.0 and 17.4 years were included. When lung functions were outside the normal range, 50% of patients was hospitalized at 4 months after the outpatient visit, and response to exercise was abnormal (100%). Half of Individuals with normal forced expiratory volume in the first second (FEV1) and abnormal lung clearance index (LCI) experienced the first hospital admission 9 months after the clinic visit, and 84.2% presented an abnormal response to exercise. Conversely, 15.8% had abnormal exercise response when lung functions were considered normal, with half of adolescents hospitalized at 11 months. Conclusion. Preserving ventilation homogeneity together with a normal ability to sustain intense work might have positive consequences on the burden of CF disease, here conceived as time free from hospitalization due to PE.